Recurrent life‐threatening reactions to platelet transfusion in an aplastic anaemia patient with a paroxysmal nocturnal haemoglobinuria clone. Issue 9 (September 2014) - Mohamed, M.; Bates, G.; Richardson, D.; Burrows, L.
Abstract A 60‐year‐old woman was diagnosed with non‐severe aplastic anaemia when she presented with anaemia and thrombocytopenia. She developed recurrent life‐threatening hypotensive reactions during transfusion of leukodepleted platelet concentrates, and washed platelet concentrates prevented the development of such reactions subsequently. A paroxysmal nocturnal haemoglobinuria clone was detected on investigating for aplastic anaemia, which has been speculated to play a role in the recurrent hypotensive reactions.